Lung Adenocarcinoma Mimicking a Bilateral Cavitary Pneumonia. Issue 1 (8th June 2022) - Mahiat, Cédric; Colinet, Benoît; Poncelet, Pierre-Antoine
Teaching Point: Failure to recognize unusual radiological presentations of some lung adenocarcinomas can lead to misdiagnosis and/or delay appropriate treatment.